REASERCH AND CASE STUDIES ON WATER LOSSES INDISTRIBUTION NETWORKS AND THEIR EFFECT ON THE GROUNDWATER (PANGEEA, 2025)
The current paper approaches the possibility of using the devices owned by the Company I work for, namely the G.P.R., U.A.V., thermal imaging camera, for the purpose of loss detection both on drinking water distribution and transportation pipes. The paper comprises a series of cases we actually encountered on site and successfully identified using the G.P.R. and pre-encountered with the thermal cameras and drones. The cases are explained, illustrated with on-site images and have been confirmed by visual inspection in the respective areas and by other devices on Mobile Laboratory for Loss Detection and by conducting surveys (mechanized excavation) at those specific points. In conclusion, the methods used in the field to identify water losses can have good results as a secondary procedure for leak detection.